Analisis Konflik Perubahan Tradisi Pra-Pernikahan “Diba’an” dalam Kelompok Masyarakat Islam Nahdlatul Ulama Desa Gading - Ayu Febriani; Agus Mahfud Fauzi (Research Institute and Community Engagement of IAIN MADURA, 2022)
Gading Village, Madiun Regency has a tradition which is a relation between the beliefs of the Nahdlatul Ulama community and local culture, namely diba'an. Generally, diba'an is understood as a prayer activity accompanied by a sermon. Meanwhile, in Gading Village, the diba'an is carried out as a series of pre-wedding rituals because it is believed to be a prayer hoping for smoothness and harmony between two couples getting married. However, due to the COVID-19 pandemic, the implementation of the diba'an tradition has changed or even been stopped and caused conflict. The purpose of this study was to analyze the conflict by using the conflict theory of Karl Marx and descriptive qualitative methods sourced from primary and secondary data. The results of the study indicate that the conflict stems from the conflict between